Role of Helicobacter Pylori in Nasal Polyp Formation: A Case-Control Study in Tehran, Iran - Reza Shokrollahi Mohammad; Tabatabaei Azardokht; Farhadi Mohammad; Noorbakhsh Samileh; Movahedi Zahra (Journal of Otolaryngology Advances, 2016)
Background and Objective: The etiological factors for nasal polyps include infection, inflammation or an imbalance of a metabolic pathway. This study was designed to compare serum Helicobacter pyloriantibodies and H. pylori–DNAs between cases of nasal polyp and controls (nasal fracture). Patients and Methods: This case control study was carried out in ENT Department of Rasul Hospital in Tehran (2007-2008), upon nasal polyp tissues in 62 cases and inferior nasal turbinate mucosa in 25 controls. H. pylori–DNAs were searched by qualitative polymerase chain reaction (PCR) and serum specific H. pylori antibodies (ELISA IgG and IgA). Comparative tests were performed for the 2 groups, and P value < 0.05 was considered as statistically significant. Results: The mean age of cases and controls were 37.5 ± 13.7 and 31 ± 11.5 years, respectively. H. pylori–DNA was found in 32.3% (20/62) of the cases and 4% (1/25) of the controls (P value = 0.005). Serum H. pylori antibody (IgA) was found in 14.5% (9/62) of the cases and 4% (1/25) of the controls (P value = 0.27). However, previous immunity (IgG) was higher in 71% of the cases and 32% of the controls (P = 0.001). Conclusion: H. pylori infection may play a key role in the formation of nasal polyps. We recommend the PCR as the best method of searching for H. pylori infection. However, from the data obtained in this investigation it could not be determined whether or not H. pylori play a pathogenic role. Long-term antibiotics treatment in cases with nasal polyp, especially in cases with severe chronic rhinosinusitis where patients do not respond to surgery or steroids, may be useful. More randomized controlled trial (RCT) studies are necessary to validate the role of H. pylori infection in nasal polyp and the effect of antibiotics for eradication of H. pylori infection.
Keywords: Nasal polyp